Synthesis, NMR spectroscopy and crystal structures studies of 2-amino-N-(2-hydroxy-3-methoxybenzylidene) aniline - Al-Douh, Mohammed Hadi; Osman, Hasnah; Abd Hamid, Shafida (2009)
The reaction of o–vanillin 1 with o-phenylenediamine 2PD, in dichloromethane at low conditions produced novel amino benzeneamine: 2-amino-N-(2-hydroxy-3-methoxybenzylidene) aniline 2. Intermediate 2 is isolated and obtained as single crystals and the structure was determined and studied by x-ray crystallography. The complete assignments of 2 were made using FTIR, HRMS, 1D and 2D NMR including APT, COSY, HMQC and HMBC in CDCl3 and will be discussed.